Nadyuk Z.O., Bezkorovayna U.Y., Nedil’ko R.V. The problem of burnout syndrome’s overcoming in the motivational mechanism of public administration in the medical sphere of Ukraine - admin, admin (Pressing Problems of Public Administration, 2019)
Initially, the burnout syndrome was considered only by social workers (health workers, teachers, social workers), today it is considered in all areas of human life without exception. One of the main mechanisms of public administration in the medical field is the motivational mechanism. To ensure the effectiveness of this mechanism, appropriate measures should be developed to support it. We offer both at national and regional levels to develop targeted programs to combat the syndrome of professional burnout from medical professionals. Such programs should contain basic theses for the entire field and vary according to the specifics of their industry